Ο ασκοθυράριος - ΔΙΑΜΑΝΤΗ Χαρίκλεια (Byzantina Symmeikta, 1998)
Charikleia Diamanti The «askothyrarios» The «askothyrarios» is mentioned in the lemma of the 22nd chapter of the Book of the Eparch among the craftsmen related to various building works. The term has been interpreted as designing the locksmiths or the «Türbelederer». Two Byzantine texts quoted by Koukoules as well as the etymological analysis of the term lead us to a new interpretation of this controversial term: We propose that by «askothyrarios» the Book of the Eparch designates the carpenter specialized in the construction or renovation of the wooden parts of the building, namely the doors.